2015
DOI: 10.3390/nu7031672
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Phytosterols and Triterpenoids with Potential Anti-Cancer Activity in Bran of Black Non-Glutinous Rice

Abstract: Structures of some bioactive phytochemicals in bran extract of the black rice cv. Riceberry that had demonstrated anti-cancer activity in leukemic cell line were investigated. After saponification with potassium hydroxide, separation of the unsaponified fraction by reversed-phase high performance liquid chromatography (HPLC) resulted in four sub-fractions that had a certain degree of anti-proliferation against a mouse leukemic cell line (WEHI-3 cell), this being IC50 at 24 h ranging between 2.80–467.11 μg/mL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 31 publications
5
66
0
Order By: Relevance
“…Extracts of red rice have been shown to limit the invasiveness of cancer cells in a dose-dependent manner (Pintha et al, 2014). The phytosterols 24-methylenecycloartanol, β-sitosterol, gramisterol, campesterol, stigmasterol, cycloeucalenol, 24-methylene-ergosta-5-en-3β-ol, and 24-methylene-ergosta-7-en-3β-ol, all of which are present in extracts of black rice bran, have also been reported to be effective as agents restricting the proliferation of murine leukemic cells (Suttiarporn et al, 2015). Consequently, one of the longterm strategies proposed by Luo et al (2014) to prevent breast cancer metastasis relies on the inclusion of pigmented rice in the human diet.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…Extracts of red rice have been shown to limit the invasiveness of cancer cells in a dose-dependent manner (Pintha et al, 2014). The phytosterols 24-methylenecycloartanol, β-sitosterol, gramisterol, campesterol, stigmasterol, cycloeucalenol, 24-methylene-ergosta-5-en-3β-ol, and 24-methylene-ergosta-7-en-3β-ol, all of which are present in extracts of black rice bran, have also been reported to be effective as agents restricting the proliferation of murine leukemic cells (Suttiarporn et al, 2015). Consequently, one of the longterm strategies proposed by Luo et al (2014) to prevent breast cancer metastasis relies on the inclusion of pigmented rice in the human diet.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…Their in vitro bioaccessibility, defined as the ratio between its concentrations in the undigested and digested samples, is the unity. This is an important fact because beneficial biological activities have been attributed to these compounds [30,37].…”
Section: In Vitro Bioaccessibility Of Some Minor Components Of Virginmentioning
confidence: 99%
“…TU-093 was also higher in γ-oryzanol than the RD6 or KDML105 check varieties, by 4.5 to 85.2 times ( Figure 3B). Vegetarian diets that are high in phytosterols are associated with a reduced risk of breast cancer [23]. β-sitosterol and campesterol are the predominant and most common sterols found in rice [8,14,35], and these fat-soluble compounds were the focus of our study.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Its analysis can support the improvement of the nutritional value of rice and the development of materials with pharmaceutical and nutraceutical applications. Previous studies have reported variability in the fat-soluble content of rice and its coproducts, but these have examined only a subset of genotypes, most of which are commercial cultivars of Thai rice [22][23][24]. The genetic diversity of rice germplasms is important when categorizing sources of variation or identifying genotypes with superior nutraceutical lipid contents.…”
mentioning
confidence: 99%